Antistatic aerogel for 3D printing and preparation method and application thereof

By in-situ polymerization of acid-doped polyaniline in polyamide acid solution and introducing modified inorganic nanoparticles, the problem of poor antistatic properties of 3D printing resin materials is solved, the conductivity and mechanical properties of the material are improved, and it is suitable for photocuring, selective laser sintering, fused deposition and layered solid manufacturing in 3D printing technology.

CN120818176AActive Publication Date: 2025-10-21SUZHOU GANGRUITONG NANO MATERIALS TECH CO LTD

Patent Information

Application Number
CN202511325033.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2025-10-21
Estimated Expiration
2045-09-17

AI Technical Summary

Technical Problem

Existing 3D printing resin materials have poor antistatic properties, which leads to charge accumulation and causes high-voltage discharge, affecting the normal operation of the equipment.

Method used

Polyamide is used as the aerogel matrix, acid-doped polyaniline is in situ polymerized in its acidic solution, and inorganic nanoparticles modified with epoxy group-containing silane coupling agent are introduced as nucleating agents to form polyaniline nanoparticles with core-shell structure, thereby improving conductivity and compatibility.

Benefits of technology

The production process is simplified, the uniform doping and dispersion of polyurethane resin materials are achieved, and the antistatic and mechanical properties of 3D printing materials are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818176A_ABST
    Figure CN120818176A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aerogel materials, and particularly relates to antistatic aerogel for 3D printing as well as a preparation method and application of the antistatic aerogel. The preparation method comprises the following steps: (1) dispersing inorganic nanoparticles modified by a silane coupling agent containing epoxy groups and an aniline monomer in an acidic solvent to obtain a monomer mixed solution; (2) stirring and dissolving polyamide in the monomer mixed solution; (3) initiating a reaction to obtain a polyaniline modified polyamide solution; and (4) freeze-drying to obtain the antistatic aerogel for 3D printing. By controlling synthesis conditions, a core-shell structure of acid-doped polyaniline coated inorganic nanoparticles is formed, and a good conductive path is formed in polyamide with a small addition amount of polyaniline. The antistatic aerogel for 3D printing can be applied to technologies such as photocuring molding and fused deposition of polyurethane resin in a 3D printing technology, and the antistatic property and the mechanical property of a 3D printed product are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aerogel materials, and in particular relates to an antistatic aerogel for 3D printing, a preparation method thereof, and an application thereof. Background Art

[0002] 3D printing is one of the most advanced additive manufacturing (AM) technologies. It involves adding and joining materials layer by layer to form a part. AM contrasts with subtractive manufacturing (SM), which involves removing material from a bulk material (i.e., machining) to create the desired product. A key advantage of AM over SM is its ability to accurately produce more complex shapes. Due to its advantages in manufacturing efficiency, scalability, and low cost, AM has attracted widespread attention in the development of advanced manufacturing materials.

[0003] With the rapid development of 3D printing technology in recent years, it has been widely applied in many fields and has made great progress. Firstly, 3D printing technology is ideal for aerospace components because they have complex geometries and need to consider the effects of structure, heat dissipation, and airflow. Customized production through 3D printing can reduce waste and provide complex shapes. The aerospace industry is characterized by the production of small batches of parts. 3D printing technology is relatively convenient and does not require expensive equipment such as molds compared to traditional technologies.

[0004] Secondly, 3D printing technology has also found widespread application in the biomedical field. 3D printing technology enables the 3D printing of biocompatible materials, cells, and supporting components into complex, 3D functional living tissues. 3D bioprinting is being applied in regenerative medicine to address the need for tissues and organs suitable for transplantation. 3D bioprinting has been used to generate and transplant a variety of tissues, including skin, bone, vascular grafts, tracheal splints, cardiac tissue, and cartilage structures.

[0005] 3D printing technology is also used in automated construction. Due to its advantages such as high precision, strong opening capacity, and various design possibilities, 3D printing has a certain degree of reliability in the construction industry, such as geometric complexity and hollow structures.

[0006] 3D printing technology, a common production method, is currently being applied in numerous fields, including clothing, electronics, automobiles, robotics, military, and oceanography. The most widely used printing materials in these 3D printing technologies are resins such as polyurethane. Polyurethane is widely used in 3D printing due to its excellent mechanical strength, toughness, and processing properties. However, as a resin material, it has poor antistatic properties. During use, charge accumulation can cause high-voltage discharge, disrupting normal equipment operation. Summary of the Invention

[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide an antistatic aerogel for 3D printing. The antistatic material has a porous gel structure, which is conducive to the full infiltration of the resin material during the printing process, improves its compatibility with materials such as polyurethane resin, and further improves its antistatic performance on the basis of improving the mechanical properties of the printed material.

[0008] To improve the antistatic properties of resins, conductive fillers are often added. The preparation methods for polymer conductive composites can be divided into two main categories based on the method of incorporating conductive fillers: in-situ polymerization and solution blending, in which the conductive filler and polymer are physically dispersed before or after polymerization to produce nanocomposites; and prefabricated conductive three-dimensional structures followed by polymer infiltration polymerization to produce polymer nanocomposites. In previous work, the inventors used in-situ polymerization (CN118667223A) and post-infiltration (CN118702962A, CN118812911A, CN118834412A, etc.) to prepare aerogel powders with moderate conductive properties. The in-situ polymerization method requires the polymerization of multiple raw materials and is complex to prepare. The post-infiltration process, on the other hand, takes longer to prepare, requiring not only the initial construction of a three-dimensional conductive matrix but also a tedious infiltration process. During this process, the infiltrating components can be unevenly dispersed, forming micron-sized aggregates, which can reduce the performance of the composite. In order to solve the above problems, the present invention uses polyamide as an aerogel matrix and directly prepares acid-doped polyaniline conductive particles in a polyamide solution.

[0009] In order to achieve the above object, the present invention adopts the following specific technical solutions: A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) Inorganic nanoparticles modified with an epoxy group-containing silane coupling agent and aniline monomers are dispersed in an acidic solvent and allowed to stand for a period of time to obtain a monomer mixed solution; specifically, the solution can be allowed to stand for 1-2 hours to promote the formation of hydrogen bonds between the aniline monomer and the epoxy group-containing silane coupling agent; (2) stirring and dissolving the polyamide in the monomer mixed solution to obtain a polyamide mixed solution; (3) adding the initiator dropwise into the polyamide mixed solution, stirring and reacting for a certain period of time to obtain a polyaniline-modified polyamide solution; (4) Freeze-drying the polyaniline-modified polyamide solution to obtain an antistatic aerogel for 3D printing. Freeze-drying technology is a simple, economical, and environmentally friendly drying method. It uses the principle of ice crystal sublimation to lower the solvent temperature to below the freezing point, turning water into ice. Then, under a high vacuum, the ice is directly sublimated into steam, which can eliminate the gas-liquid interface and avoid the formation of a curved liquid surface in the pores, thereby reducing the drying stress and obtaining an aerogel with a complete skeleton. In particular, after the reaction is completed, it can be heated appropriately to promote the dispersion of the components before freeze-drying.

[0010] The present invention chooses polyamide as the matrix resin for antistatic aerogels for 3D printing because structural differences between polymers directly reflect their compatibility. Polyurethane is a block polymer with urethane bonds as repeating units, while the characteristic group in polyamide is amide bonds. Urethane and amide bonds have similar structures and can act as hydrogen bond donors and acceptors for each other. Therefore, structurally, polyurethane and polyamide have good compatibility. Polyurethane and polyamide also have their own performance advantages. Polyurethane, due to microphase separation, possesses unique properties such as high tensile strength, high elongation at break, good wear resistance, and low-temperature elasticity. Polyamide, on the other hand, has excellent mechanical, electrical, and thermal properties and exhibits high temperature resistance. Both polyurethane and polyamide can serve as secondary components to enhance the performance of the other. Furthermore, polyamide generally has a high melting point (generally above 240°C) and high tensile strength. Using polyamide as the matrix structure of the aerogel can improve the mechanical properties of the aerogel, thereby enhancing the mechanical strength of the polyurethane composite. More importantly, compared with thermoplastic resin materials such as polyimide and polyurethane, polyamide is soluble in acidic solvents. While intrinsic polyaniline and its derivatives are electrical insulators with low electrical conductivity, after being doped with protonic acid, their electrical conductivity can be improved by ten orders of magnitude. The doping process of polyaniline is reversible. When polyaniline is doped with protonic acid, only positive charge is introduced without changing the number of electrons on its main chain. That is, there is only the transfer of protons, which is essentially an intramolecular redox reaction. The electronic structure has also undergone significant changes. During doping, the imino groups on the molecular chain form semi-ketone radical cations with the protonic acid. Simultaneously, electron transfer on the nitrogen atom forms a conductive bipolaron lattice, making the polyaniline conductive. The present invention in situ polymerizes polyaniline in a polyamide acid solution, cleverly and directly utilizing the acidic solvent in the polyamide solution to dope the polyaniline, not only simplifying the production process, but also making the acid-doped polyaniline uniformly dispersed in the polyamide matrix.

[0011] However, polyaniline synthesized by directly adding aniline monomer to a polyamic acid solution has poor dispersibility and difficulty forming a conductive path. To uniformly disperse polyaniline in the polyamide aerogel network, the present invention introduces inorganic nanoparticles modified with epoxy-containing silane coupling agents as nucleating agents for polyaniline. Furthermore, as rigid particles, the inorganic nanoparticles modified with epoxy-containing silane coupling agents can play a reinforcing role, improving the mechanical properties of the polyamide-based aerogel powder. The epoxy groups on the surface of the inorganic nanoparticles modified with epoxy-containing silane coupling agents easily form hydrogen bonds with the amino groups on the aniline monomer. When an initiator is added, the aniline monomer forms polyaniline-coated inorganic nanoparticles with the inorganic nanoparticles modified with epoxy-containing silane coupling agents as cores. This polyaniline-modified inorganic nanoparticle formed by in-situ polymerization in a polyamic acid solution takes into account the triple technical effects of doping, reinforcement, and conductivity: first, the polyamide dissolved in the acid solution serves as the matrix resin of the aerogel and plays a skeleton role; second, the acid in the polyamide solution not only dissolves the polyamide, but also dopes the polyaniline to improve the conductivity of the polyaniline; and the inorganic nanoparticles modified with a silane coupling agent containing epoxy groups not only reinforce the rigid particles, but more importantly, they can serve as nucleating agents for aniline monomers, forming polyaniline nanoparticles with a core-shell structure in situ in the polyamide solution, improving the dispersion properties of the polyaniline, promoting the formation of conductive paths, and greatly improving the conductivity of the aerogel with the addition of less conductive filler. Conversely, the polyaniline on the surface of inorganic particles not only enhances conductivity, but also has good compatibility with polyurethane and polyamide, all of which are nitrogen-containing organic substances. Using polyaniline to coat inorganic nanoparticles can improve the compatibility of inorganic nanoparticles with resins such as polyamide and polyurethane, and improve dispersion and mechanical properties.

[0012] It is important to note the order in which the inorganic nanoparticles modified with the epoxy-containing silane coupling agent and the aniline monomer are added. First, an acidic solution of the inorganic nanoparticles modified with the epoxy-containing silane coupling agent and the aniline monomer should be prepared. Then, the polyamide should be added to the acidic solution to gradually dissolve the polyamide. If the inorganic nanoparticles modified with the epoxy-containing silane coupling agent and the aniline monomer are added directly to the acidic polyamide solution, the presence of nitrogen-containing groups in the polyamide will affect the nucleation of the inorganic nanoparticles modified with the epoxy-containing silane coupling agent, hindering the formation of the organic-inorganic core-shell structure.

[0013] In one embodiment, the epoxy group-containing silane coupling agent in step (1) is at least one of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. Compared with amino group-containing silane coupling agents, epoxy groups contain more active oxygen-containing ether bonds, which can form hydrogen bonds with amino groups on aniline monomers, forming a stronger bonding effect, so that the inorganic nanoparticles can play a nucleating role and are not affected by the nitrogen-containing polymer polyamide in the formic acid solution. However, the amino groups on the silane coupling agent do not have oxygen-containing active functional groups and are not easy to form hydrogen bonds or other bonding effects with aniline monomers that also contain amino groups. In addition, they are easily affected by polyamide in the solution. Therefore, they can only play a role in improving the compatibility of inorganic nanoparticles with the matrix resin and cannot play a nucleating role.

[0014] In one embodiment, the inorganic nanoparticles in step (1) are at least one of nano-silicon dioxide, nano-zirconium dioxide, nano-silicon carbide, nano-silicon nitride, and nano-boron carbide.

[0015] In one embodiment, the inorganic nanoparticles have a particle size of 10-100 nm. Specifically, the inorganic nanoparticles may have a particle size of any value ranging from 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, or 100 nm. Inorganic nanoparticles of an appropriate particle size can achieve both nucleation, dispersion, and reinforcement, thereby improving the mechanical properties of the 3D printed antistatic material.

[0016] In one embodiment, the acidic solvent is a formic acid solution. Specifically, a formic acid aqueous solution with a concentration of 88 wt % can be used.

[0017] In one embodiment, the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer in step (1) is (0.05-0.5):1. The surface of the modified inorganic nanoparticles is rich in epoxy groups, which easily form hydrogen bonds with the amino groups on the aniline monomer, thereby enhancing the nucleation effect of the inorganic nanoparticles. In particular, the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is (0.05-0.4):1; further, (0.1-0.35):1; and further, (0.1-0.3):1. An appropriate amount of inorganic nanoparticles can not only play a role in strengthening the rigid particles and forming nuclei, but also avoid the problem of excessive particle agglomeration and incomplete polyaniline coating, promote the formation of the polyaniline core-shell structure, and improve the compatibility of the inorganic nanoparticles with the polyamide resin.

[0018] In one embodiment, the specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent in step (1) is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and the inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 40-60° C. for 1-2 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent.

[0019] In one embodiment, the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles in step (1) is (0.5-1):1.

[0020] In one embodiment, the polyamide in step (2) is at least one of polyamide 6, polyamide 66, polyamide 46, polyamide 56, polyamide 610, polyamide 1010, and polyamide 12.

[0021] In one embodiment, the polyamide concentration in the polyamide mixed solution in step (2), that is, the mass ratio of polyamide to solvent, is 1-10 wt %.

[0022] In one embodiment, the mass ratio of aniline monomer to polyamide in step (2) is (0.2-0.8):1. Specifically, it can be any value among 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1 or 0.8:1. If the amount of polyaniline monomer is too small, it is not conducive to the formation of conductive paths and the antistatic performance is poor; if the amount is too large, it is easy to affect the structure of the aerogel and is not conducive to improving the mechanical properties of the 3D printed product.

[0023] In one embodiment, the initiator in step (3) is at least one of ammonium persulfate and potassium persulfate; specifically, the initiator is added dropwise in the form of an aqueous solution.

[0024] In one embodiment, the molar ratio of the initiator to the aniline monomer in step (3) is (0.1-1):1.

[0025] In one embodiment, the reaction temperature in step (3) is 0-5°C, and the reaction time is 10-20 hours.

[0026] On the other hand, the present invention also provides an antistatic aerogel for 3D printing prepared by the above method. The material is an aerogel material with a three-dimensional porous structure. Using the aerogel material as a reinforcing and antistatic filler for 3D printing resin materials such as polyurethane can improve the mechanical properties and antistatic ability of the printed products.

[0027] In addition, the present invention also provides an application of the antistatic aerogel for 3D printing and a prepared 3D printing polyurethane material. The antistatic aerogel for 3D printing can be used in the photocuring molding technology, selective laser sintering technology, fused deposition technology or layered entity manufacturing technology in 3D printing technology. Specifically, the 3D printing polyurethane material comprises a polyurethane resin material and an antistatic aerogel for 3D printing. Furthermore, photocuring molding technology or fused deposition technology can be used. In particular, the polyurethane material is prepared by fused deposition technology. Among them, the printing temperature in the fused deposition technology is not particularly limited, generally between 190-220°C, and can be adjusted according to the production process.

[0028] The synthesis of the antistatic aerogel for 3D printing of the present invention first involves effective control of the geometric parameters (particle size and particle size distribution), spatial distribution parameters (uniformity), and volume fraction (content) of the polyaniline nanoparticles in the composite system. In particular, the synthesis conditions are controlled to ensure that the polyaniline particles in the system are within the nanoscale range in at least one dimension (i.e., the primary structure of the nanoparticles is controlled). Secondly, the secondary structure of the nanoparticle aggregates is controlled, which includes controlling the agglomeration of the modified polyaniline nanoparticles and the distribution of the nanoparticles in the polyamide matrix resin material. This allows a good conductive path to be formed with a relatively small amount of polyaniline added, thereby improving the antistatic properties of the antistatic aerogel for 3D printing.

[0029] Beneficial effects: The present invention in situ polymerizes polyaniline in a polyamide acidic solution, cleverly utilizing the acidic solvent in the polyamide solution to dope the polyaniline. This not only simplifies the production process but also allows the acid-doped polyaniline to be uniformly dispersed in the polyamide matrix. The present invention introduces inorganic nanoparticles modified with an epoxy-containing silane coupling agent as nucleating agents for the polyaniline and as rigid particle reinforcements for the polyamide-based aerogel powder. The inorganic nanoparticles modified with an epoxy-containing silane coupling agent act as nucleating agents for the aniline monomer, forming polyaniline nanoparticles with a core-shell structure in situ in the polyamide solution. This improves the dispersion of the polyaniline, promotes the formation of conductive pathways, and significantly enhances the conductivity of the aerogel with minimal addition of conductive filler. By controlling the agglomeration of the modified polyaniline nanoparticles and the distribution of the nanoparticles within the polyamide matrix resin material, a good conductive pathway is formed with minimal addition of polyaniline, thereby enhancing the antistatic properties of the antistatic aerogel for 3D printing. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the antistatic aerogel for 3D printing prepared in Example 10; Figure 2 This is a transmission electron micrograph of particles obtained by acid dissolution of the antistatic aerogel for 3D printing prepared in Example 10; Figure 3 This is a transmission electron micrograph of particles obtained by acid dissolution of the antistatic aerogel for 3D printing prepared in Comparative Example 1.

[0031] in, Figure 2 and Figure 3 The specific preparation method of the particles is as follows: the antistatic aerogels for 3D printing prepared in Example 10 and Comparative Example 1 are respectively ultrasonically dissolved and dispersed in a formic acid solution, and filtered to obtain a precipitate; then washed with a large amount of deionized water to obtain a precipitate aqueous dispersion; the precipitate is separated by centrifugation, and due to the high density of silica, it settles at the bottom; the precipitate at the bottom is taken and dried to obtain particles. DETAILED DESCRIPTION

[0032] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present application belongs.

[0033] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below with reference to specific embodiments.

[0034] Example 1 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) After the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent and the aniline monomer are stirred and dispersed in a formic acid solvent, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is 0.1:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and the inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 40° C. for 2 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.5:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 50 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.2:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.6:1; the reaction temperature is 0°C, and the reaction time is 13 h.

[0035] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0036] Example 2 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) Inorganic nanoparticles modified with epoxy group-containing silane coupling agent and aniline monomer were stirred and dispersed in formic acid solvent, and then allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of inorganic nanoparticles modified with epoxy group-containing silane coupling agent to aniline monomer was 0.35:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and the inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 60° C. for 1 hour, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 1:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltriethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 50 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.62:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.9:1; the reaction temperature is 0°C, and the reaction time is 20 h.

[0037] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0038] Example 3 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) After the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent and the aniline monomer are stirred and dispersed in a formic acid solvent, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is 0.05:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 50° C. for 1.6 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.8:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 40 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.48:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.8:1; the reaction temperature is 0°C, and the reaction time is 17 h.

[0039] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0040] Example 4 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) Inorganic nanoparticles modified with epoxy group-containing silane coupling agent and aniline monomer were stirred and dispersed in formic acid solvent, and then allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of inorganic nanoparticles modified with epoxy group-containing silane coupling agent to aniline monomer was 0.12:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and the inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 48° C. for 1.6 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 1:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltriethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 35 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.58:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.9:1; the reaction temperature is 0°C, and the reaction time is 10 h.

[0041] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0042] Example 5 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) After the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent and the aniline monomer are stirred and dispersed in a formic acid solvent, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is 0.5:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 50° C. for 1.6 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.8:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 40 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.48:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.8:1; the reaction temperature is 0°C, and the reaction time is 17 h.

[0043] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0044] Example 6 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) After the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent and the aniline monomer are stirred and dispersed in a formic acid solvent, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is 0.17:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and the inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 45° C. for 1.7 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.6:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltriethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 40 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.4:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.7:1; the reaction temperature is 0°C, and the reaction time is 15 h.

[0045] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0046] Example 7 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) After the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent and the aniline monomer are stirred and dispersed in a formic acid solvent, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is 0.2:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 50° C. for 1.6 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.8:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 40 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.8:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.8:1; the reaction temperature is 0°C, and the reaction time is 17 h.

[0047] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0048] Example 8 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) After the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent and the aniline monomer are stirred and dispersed in a formic acid solvent, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is 0.25:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and the inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 55° C. for 1.3 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.8:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 50 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.55:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.7:1; the reaction temperature is 0°C, and the reaction time is 17 h.

[0049] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0050] Example 9 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) Inorganic nanoparticles modified with epoxy group-containing silane coupling agent and aniline monomer were stirred and dispersed in formic acid solvent, and then allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of inorganic nanoparticles modified with epoxy group-containing silane coupling agent and aniline monomer was 0.3:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and the inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 47° C. for 1.4 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.7:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltriethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 60 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.43:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.7:1; the reaction temperature is 0°C, and the reaction time is 19 h.

[0051] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0052] Example 10 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) After the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent and the aniline monomer are stirred and dispersed in a formic acid solvent, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is 0.2:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 50° C. for 1.6 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.8:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 40 nm; (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.48:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.8:1; the reaction temperature is 0°C, and the reaction time is 17 h.

[0053] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0054] Comparative Example 1 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) After the inorganic nanoparticles modified with the amino group silane coupling agent and the aniline monomer are stirred and dispersed in a formic acid solvent, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the amino group silane coupling agent to the aniline monomer is 0.2:1; The specific preparation process of the inorganic nanoparticles modified with an amino group-containing silane coupling agent is as follows: uniformly dispersing the amino group-containing silane coupling agent and inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 50° C. for 1.6 hours, filtering, washing, and drying to obtain inorganic nanoparticles modified with an amino group-containing silane coupling agent; the mass ratio of the amino group-containing silane coupling agent to the inorganic nanoparticles is 0.8:1; the amino group-containing silane coupling agent is γ-aminopropyltriethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 40 nm. (2) stirring and dissolving polyamide in the monomer mixed solution to obtain a polyamide mixed solution; the polyamide is polyamide 66; the polyamide concentration in the polyamide mixed solution is 3.5 wt%; and the mass ratio of aniline monomer to polyamide is 0.48:1; (3) Add ammonium persulfate initiator dropwise into the polyamide mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of the initiator to the aniline monomer is 0.8:1; the reaction temperature is 0°C, and the reaction time is 17 h.

[0055] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0056] Comparative Example 2 A method for preparing antistatic aerogel for 3D printing comprises the following steps: (1) stirring and dissolving polyamide in a formic acid solvent to obtain a polyamide mixed solution; the polyamide is polyamide 66; and the polyamide concentration in the polyamide mixed solution is 3.5 wt%; (2) After the inorganic nanoparticles modified with the epoxy group silane coupling agent and the aniline monomer are stirred and dispersed in the polyamide mixed solution, the mixture is allowed to stand for 1.5 hours to obtain a monomer mixed solution; the mass ratio of the inorganic nanoparticles modified with the epoxy group silane coupling agent and the aniline monomer is 0.2:1; the mass ratio of the aniline monomer to the polyamide is 0.48:1; The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 50° C. for 1.6 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent; the mass ratio of the epoxy group-containing silane coupling agent to the inorganic nanoparticles is 0.8:1; the epoxy group-containing silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; the inorganic nanoparticles are nano-silica; and the volume average particle size D50 of the inorganic nanoparticles is 40 nm; (3) Add ammonium persulfate initiator dropwise into the monomer mixed solution and stir the reaction for a certain time to obtain a polyaniline modified polyamide solution; the molar ratio of initiator to aniline monomer is 0.8:1; the reaction temperature is 0°C, and the reaction time is 17 h.

[0057] (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

[0058] The performance testing method of the aerogel materials prepared in the above examples and comparative examples is as follows: under the same conditions, the effects of the antistatic aerogels for 3D printing prepared in Examples 1-10 and Comparative Examples 1-2 on the performance of 3D printed polyurethane products are tested.

[0059] Specifically, the 3D printing polyurethane material contained 100 parts thermoplastic polyurethane, 15 parts antistatic aerogel for 3D printing, and 3 parts zinc stearate. The 3D printing polyurethane material was printed into strips. The tensile strength of the strips was tested according to GB / T528-2009, Rubber (vulcanized or thermoplastic) — Determination of tensile stress-strain properties, and the electrical conductivity was tested using a conductivity meter. The results are shown in Table 1.

[0060] Table 1 3D printing polyurethane product performance corresponding to Examples 1-10 and Comparative Examples 1-2 Table 1 Figure 1This is a scanning electron micrograph of the antistatic aerogel for 3D printing prepared in Example 10. As can be seen from the image, the aerogel has a rich pore structure with relatively uniform pore size, which facilitates melt impregnation of thermoplastic resins such as polyurethane, improving the compatibility and interfacial interaction between the aerogel and the 3D printing matrix resin.

[0061] Figure 2 This is a transmission electron micrograph of the particles obtained by acid dissolution of the antistatic aerogel for 3D printing prepared in Example 10. The image shows that polyaniline is uniformly coated on the surface of the dense silica particles, not only providing conductivity but also acting as a surface modifier for the inorganic nanoparticles, improving their compatibility with the organic polyamide resin, enhancing the stability of the aerosol, and improving the mechanical properties of the 3D printing material.

[0062] Figure 3 This is a transmission electron microscope image of the particles obtained by acid dissolution of the antistatic aerogel for 3D printing prepared in Comparative Example 1. Figure 3 It can be seen that the surface of the inorganic nanoparticles is relatively smooth and there is no obvious coating layer, which means that polyaniline does not undergo polymerization reaction on the surface of the inorganic nanoparticles and does not form a core-shell structure.

[0063] At the same time, combined with the data in Table 1, it can be seen that the present invention in situ polymerizes polyaniline in a polyamide acidic solution, cleverly utilizing the acidic solvent in the polyamide solution to dope the polyaniline. This not only simplifies the production process but also allows the acid-doped polyaniline to be uniformly dispersed in the polyamide matrix. The present invention introduces inorganic nanoparticles modified with an epoxy-containing silane coupling agent as nucleating agents for polyaniline and as rigid particle reinforcements for polyamide-based aerogel powders. These inorganic nanoparticles modified with an epoxy-containing silane coupling agent act as nucleating agents for the aniline monomer, forming polyaniline nanoparticles with a core-shell structure in situ in the polyamide solution. This improves the dispersion of the polyaniline, promotes the formation of conductive pathways, and significantly enhances the conductivity of the aerogel with minimal addition of conductive filler. By controlling the agglomeration of the modified polyaniline nanoparticles and the distribution of the nanoparticles within the polyamide matrix resin material, a good conductive pathway is formed with minimal addition of polyaniline, thereby improving the antistatic properties of antistatic aerogels for 3D printing.

[0064] Specifically, compared to Example 10, Comparative Example 1 used an amino-group-containing silane coupling agent to modify the nano-silica. In the formic acid solution, the amino groups on the silane coupling agent were unable to form a strong bond with the aniline monomer, and the inorganic nanoparticles failed to act as a nucleating agent, instead simply functioning as an inorganic filler. Furthermore, the polyaniline simply acted as a conductive filler, preventing the polyaniline and inorganic nanoparticles from achieving a synergistic enhancement or antistatic effect.

[0065] Compared with Example 10, in Comparative Example 2, the polyamide was dissolved in an acidic solvent in advance, and then the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent and the aniline monomer were added to the acidic solution of the polyamide. Due to the influence of the nitrogen-containing groups in the polyamide and the high viscosity of the polymer, the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent were not conducive to the nucleation effect, resulting in poor dispersibility of the inorganic nanoparticles, and the polyaniline could not form a stable conductive network, resulting in reduced conductivity and mechanical properties of the 3D printed product.

[0066] The above description is only a preferred embodiment of the invention and is not intended to limit the scope of the invention. That is, any equivalent changes and modifications made according to the content of the patent application of the present invention should fall within the technical scope of the present invention.

Claims

1. A method for preparing antistatic aerogel for 3D printing, characterized in that: The following steps are involved: (1) dispersing inorganic nanoparticles modified with a silane coupling agent containing an epoxy group and aniline monomer in an acidic solvent, and allowing the mixture to stand for a period of time to obtain a monomer mixed solution; (2) stirring and dissolving the polyamide in the monomer mixed solution to obtain a polyamide mixed solution; (3) adding the initiator dropwise into the polyamide mixed solution, stirring and reacting for a certain period of time to obtain a polyaniline-modified polyamide solution; (4) Freeze-drying the polyaniline-modified polyamide solution to obtain antistatic aerogel for 3D printing.

2. The method for preparing an antistatic aerogel for 3D printing according to claim 1, wherein: The epoxy group-containing silane coupling agent in step (1) is at least one of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

3. The method for preparing an antistatic aerogel for 3D printing according to claim 1, wherein: The inorganic nanoparticles in step (1) are at least one of nano-silicon dioxide, nano-zirconium dioxide, nano-silicon carbide, nano-silicon nitride, and nano-boron carbide; and the particle size of the inorganic nanoparticles is 10-100 nm.

4. The method for preparing an antistatic aerogel for 3D printing according to claim 1, wherein: In the step (1), the mass ratio of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent to the aniline monomer is (0.05-0.5):

1.

5. The method for preparing an antistatic aerogel for 3D printing according to claim 1, wherein: The specific preparation process of the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent in step (1) is as follows: uniformly dispersing the epoxy group-containing silane coupling agent and the inorganic nanoparticles in a mixed solvent of ethanol and deionized water, stirring and reacting at 40-60° C. for 1-2 hours, filtering, washing, and drying to obtain the inorganic nanoparticles modified with the epoxy group-containing silane coupling agent.

6. The method for preparing an antistatic aerogel for 3D printing according to claim 1, wherein: The mass ratio of aniline monomer to polyamide in step (2) is (0.2-0.8):

1.

7. The method for preparing an antistatic aerogel for 3D printing according to claim 1, wherein: The initiator in step (3) is at least one of ammonium persulfate and potassium persulfate.

8. An antistatic aerogel for 3D printing, characterized in that: The antistatic aerogel for 3D printing is prepared by the preparation method of any one of claims 1 to 7.

9. An application of the antistatic aerogel for 3D printing according to claim 8, characterized in that: The antistatic aerogel for 3D printing is used in photocuring technology, selective laser sintering technology, fused deposition technology or layered entity manufacturing technology in 3D printing technology.

10. A 3D printing polyurethane material, characterized in that: It comprises a polyurethane resin material and an antistatic aerogel for 3D printing; the antistatic aerogel for 3D printing is the antistatic aerogel for 3D printing according to claim 8.

Citation Information

Patent Citations

  • Polyimide graphene gel powder as well as preparation method and application thereof

    CN118702962A

  • Nylon carbon nanotube graphene aerogel as well as preparation method and application thereof

    CN118812911A

  • Conductive gel powder as well as preparation method and application thereof

    CN118834412A

  • Aqueous epoxy antistatic coating with nano-core-shell structural conductive polyaniline and preparation method thereof

    CN102492349A

  • Silicon carbide / sulfonated graphene / polyaniline composite wear-resistant anticorrosive paint and preparation method thereof

    CN105504693A

Cited By

  • Nylon aerogel for 3D printing and preparation method and application thereof

    CN121159933A

  • Nylon aerogel for 3D printing and preparation method and application thereof

    CN121159933B

  • High-performance nylon aerogel for 3D printing as well as preparation method and application of high-performance nylon aerogel

    CN121181992A

  • High-performance nylon aerogel for 3D printing and preparation method and application thereof

    CN121181992B

  • Curved polyaniline modified 3D printing polyurethane material and application thereof

    CN121182184A